PERHITUNGAN NILAI KALOR BRIKET DAN KANDUNGAN HARA KOMPOS DARI LIMBAH PEMBUKAAN LAHAN TANPA BAKAR DI LAHAN GAMBUT - Muhammad Naparin; Muhammad Helmi; Fonny Rianawati; Fatriani Fatriani (Jurnal Hutan Tropis, 2019)
This study aims to determine charcoal briquette value and nutrient content of compost derived from land clearing waste on peat land in an effort to control forest and land fires that occured on peatlands. This research was carried out in a wetland area located in North Landasan Ulin, Liang Anggang sub-district, Banjar Regency because each year this location always experiences forest fires, because there are land clearing activities for plantation and agricultural activities by the community as a whole and integrated various aspects. The object of this study is Bricket and compost that made from land cleaning waste such as tree stumps, branches and twigs that used for briquette, while ferns, litter and grass were used to make compost. Based on the results of laboratory tests on the charcoal of briquette and nutrient content of compost it is known that the average of charcoal briquette value is 6.180,41 cal/gr which meet calorific value standard of charcoal briquette made in Japan which ranges from 6.000-7.000 cal/gr and Indonesian National Standard (SNI 01-6235-2000) for charcoal briquettes which is at least 5000 cal/gr, but does not fulfilled to English Standards (7.300 kal/gr) and America Standards (6.500 cal/gr). The average nutrient content of compost produced from land opening waste is N-total of 2,086%; P2O5 of 1,63%; K2O of 1,19%; ratio of C/N of 8,72 and moisture content of 24,11 (%) .